2015
DOI: 10.1590/s0100-736x2015000400001
|View full text |Cite
|
Sign up to set email alerts
|

Estudo eletrocardiográfico de éguas da raça Crioula

Abstract: RESUMO.-A eletrocardiografia constitui ferramenta indispensável no diagnóstico de arritmias e distúrbios de condução elétrica do coração de equinos, bem como na determinação do prognóstico de cardiopatias, do desempenho atlético, da eficiência do treinamento, além de sugerir distúrbios eletrolíticos. No entanto, as variáveis eletrocardiográficas em equinos podem sofrer influência de diversos fatores como a idade, sexo, raça e constituição morfofuncional, dentre outas, tornando-se necessário conhecer as caracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, it did not occur in the pregnant Creole mares studied by Pascon et al (2015). The physiological changes that occur with pregnancy include increased blood volume and cardiac output, which are associated with myocardial hypertrophy, as well as decreased peripheral resistance and an increase in uterine vascular blood flow.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, it did not occur in the pregnant Creole mares studied by Pascon et al (2015). The physiological changes that occur with pregnancy include increased blood volume and cardiac output, which are associated with myocardial hypertrophy, as well as decreased peripheral resistance and an increase in uterine vascular blood flow.…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, a smaller heart size corresponds to a higher HR and a shorter duration of the P-wave. Pascon et al (2015) studied 84 healthy Creole mares (34 pregnant and 50 non-pregnant) of three different ages. The authors demonstrated that age affected only QRS duration and that pregnancy was capable of decreasing the indexes of HR variability in the time domain, which could have influenced the electrocardiographic evaluation of the enrolled Creole mares.…”
Section: Discussionmentioning
confidence: 99%